Community rights, conservation and contested land : the politics of natural resource governance in Africa - Nelson, Fred, 1976- (London ; Washington, DC : Earthscan, 2010)
"Natural resource governance is central to the outcomes of biodiversity conservation efforts and to patterns of economic development, particularly in resource-dependent rural communities. The institutional arrangements that define natural resource governance are outcomes of political processes, whereby numerous groups with often-divergent interests negotiate for access to and control over resources. These political processes determine the outcomes of resource governance reform efforts, such as widespread attempts to decentralize or devolve greater tenure over land and resources to local communities. This volume examines the political dynamics of natural resource governance processes through a range of comparative case studies across east and southern Africa. These cases include both local and national settings, and examine issues such as land rights, tourism development, wildlife conservation, participatory forest management, and the impacts of climate change, and are drawn from both academics and field practitioners working across the region."--Publisher's description.
Introduction: the politics of natural resource governance in Africa / Fred Nelson -- Agrarian social change and post-colonial natural resource management interventions in Southern Africa's 'communal tenure' regimes / James C. Murombedzi -- The politics of community-based natural resource management in Botswana / Liz Rihoy and Brian Maguranyanga -- Peasants' forests and the king's game? Institutional divergence and convergence in Tanzania's forestry and wildlife sectors / Fred Nelson and Tom Blomley -- The evolution of Namibia's communal conservancies / Brian Jones -- Historic and contemporary struggles for a local wildlife governance regime in Kenya / Ngeta Kabiri -- Windows of opportunity or exclusion? Local communities in the great Limpopo Transfrontier Conservation Area, South Africa / Webster Whande -- 'People are not happy': crisis, adaptation and resilience in Zimbabwe's CAMPFIRE programme / Liz Rihoy, Chaka Chirozva and Somon Anstey -- The rise and fall of community-based natural resource management in Zambia's Luangwa Valley: an illustration of micro- and macro-governance issues / Rodgers Lubilo and Brian Child -- External agency and local authority: facilitating CBNRM in Mahel, Mozambique / Marta Monjane -- Adaptive or anachronistic? Maintaining indigenous natural resource governance systems in northern Botswana / Masego Madzwamuse -- Pastoral activists: negotiating power imbalances in the Tanzanian Serengeti / Maanda Ngoitiko ... [et al.] -- A changing climate for community resource governance: threats and opportunities from climate change and the emerging carbon market / Maxwell Gomera, Liz Rihoy and Fred Nelson -- Democratizing natural resource governance: searching for institutional change / Fred Nelson.
Includes bibliographical references and index.
Keywords: Nature conservation -- Government policy -- Africa; Conservation of natural resources -- Government policy -- Africa; Biodiversity -- Government policy -- Africa; Land tenure -- Africa; Community development -- Africa; Political participation -- Africa; Africa -- Environmental conditions; Africa -- Politics and government